A Halloween gene noppera-bo encodes a glutathione S-transferase essential for ecdysteroid biosynthesis via regulating the behaviour of cholesterol in Drosophila. - Enya, S.; Ameku, T.; Igarashi, F.; Iga, M.; Kataoka, H.; Shinoda, T.; Niwa, R. (Scientific reports, 2014)
In insects, the precise timing of moulting and metamorphosis is strictly guided by ecdysteroids that are synthesised from dietary cholesterol in the prothoracic gland (PG). In the past decade, several ecdysteroidogenic enzymes, some of which are encoded by the Halloween genes, have been identified and characterised. Here, we report a novel Halloween gene, noppera-bo (nobo), that encodes a member of the glutathione S-transferase family. nobo was identified as a gene that is predominantly expressed in the PG of the fruit fly Drosophila melanogaster. We generated a nobo knock-out mutant, which displayed embryonic lethality and a naked cuticle structure. These phenotypes are typical for Halloween mutants showing embryonic ecdysteroid deficiency. In addition, the PG-specific nobo knock-down larvae displayed an arrested phenotype and reduced 20-hydroxyecdysone (20E) titres. Importantly, both embryonic and larval phenotypes were rescued by the administration of 20E or cholesterol. We also confirm that PG cells in nobo loss-of-function larvae abnormally accumulate cholesterol. Considering that cholesterol is the most upstream material for ecdysteroid biosynthesis in the PG, our results raise the possibility that nobo plays a crucial role in regulating the behaviour of cholesterol in steroid biosynthesis in insects.